Accuracy of Three-Dimensional Computer-Aided Implant Surgical Guides: A Prospective In Vivo Study of the Impact of Template Design - Noel Vartan; Lotta Gath; Manuel Olmos; Konstantin Plewe; Christoph Vogl; Marco Rainer Kesting; Manfred Wichmann; Ragai Edward Matta; Mayte Buchbender (Dentistry Journal)
Background: Digital planning and the use of a static surgical guide for implant placement provide predictability and safety for patients and practitioners. The aim of this study was to investigate differences in the accuracy and fit of long and short guides. Methods: In patients with at least one missing tooth, long (supported by the entire dental arch) and short templates (supported by two teeth, mesial and distal) were compared via intraoral scans and the superimposition of the STL files of the initial planning and the actual position in the patient’s mouth along the X-, Y- and Z-axes. Furthermore, this study evaluated the conditions (e.g., mouth opening, the implant position) under which fully guided implantation can be realized. Results: The largest deviation was observed in the Z-axis, although this deviation was not as high for the short templates (0.2275 mm) as it was for the long templates (0.4007 mm). With respect to the 3D deviation (dXYZ), the average deviation from the mean value was 0.2953 mm for the short guides and 0.4360 mm for the long guides (p = 0.002). The effect size (Cohen’s d) was 0.709, which was between the medium (0.50) and large effect sizes (0.80). The shorter templates showed a smaller deviation from the actual plan by 80%. With a mouth opening ≥50 mm, fully guided surgery can be performed in the molar region. In the premolar region, the lower limit was 32 mm. Conclusions: The 3D accuracy was significantly higher for the shorter template, which could therefore be favored.